Perceptions of the Judiciary's Performance in Serbia : Results of the Survey with the General Public, Enterprises, Lawyers, Judges, Prosecutors, and Court Administrative Staff - World Bank (Washington, DC, 2015)
With the purpose of providing assistance to government efforts in justice sector reform and modernization, the World Bank conducted two surveys. The first survey was conducted in 2010 in order to collect baseline information on perceptions of the court and prosecutorial performance and expectations from the reform implemented in January 2010. The second, follow-up, survey was conducted in 2013 in order to identify the impact of the first four years (2010 - 2013) of reforms and the expectations from the new national strategy of reform for the period 2014-2018. The surveys aimed to measure perceptions of judicial performance against five core values (efficiency, quality, fairness, accessibility, and integrity - independence and presence of corruption), and to compare the views of multiple stakeholders (court services users - general public and business sector, court services providers -judges, prosecutors and providers of court administrative services, and lawyers as intermediaries between users and providers of court services). The survey also focused on costs of judicial services, with respect to perceptions of accessibility of court services, and views of cost, with respect to quality of the delivered services, from the point of view of users with experience with court cases. Surveys can map experiences, perceptions, and expectations from the point of view of various stakeholders, thus providing an indication of the judiciary's popular legitimacy that cannot be measured in other ways. The introductory section contains an overview of perceptions of the five dimensions of judiciary performance across survey groups and across time. The second section on quality, besides perceptions of overall quality of judiciary services, encompasses the perceptions of fairness, integrity (presence of corruption and independence) and impartiality, and public trust in judiciary, while the cost issue is presented in the section on accessibility. Third section presents access to judicial services. Perceptions of performance of court administrative services alongside the five dimensions by users and providers of the services are presented in a separate section four. Section five is perceptions of the reform launched in January 2010 and new national judicial reform strategy for the period 2014-2018. The final section deals with the perceived role of media in shaping the public opinion on judiciary system in Serbia.